The role of primary care in colorectal cancer screening: experience from Czech Republic - Seifert, B; Zavoral, M; Fric, P; Bencko, V (Neoplasma, 2008)
Several programmes proven to be effective in the secondary prevention of colorectal cancer (CRC) have already been introduced in Europe, each varying involvement of general practitioners. This paper reviews current screening strategies for CRC from the primary care perspective, looking at the implementation of screening strategies in Europe, focusing on screening programmes based on the faecal occult blood testing (FOBT), and drawing from experiences in the Czech Republic. We used data on CRC screening from the survey The Burden of Gastrointestinal Diseases in Europe, which was undertaken by the Public Affairs Committee of the United European Gastroenterology Federation in 2003. The data were updated by members of European Society for Primary Care Gastroenterology in 2006. For a description of the Czech screening programme, data from General Health Insurance Fund were used. Specific primary care aspects were studied in the research network of 54 general practice settings in the Czech Republic. National screening programmes have been introduced in several countries, such as Germany, the Czech Republic, Slovakia and Poland. Several important aspects of screening require monitoring: target population adherence, GPs involvement, assessment of FOBT positive rate, interdisciplinary cooperation, patient compliance and the eligibility of patients for screening. The average population adherence to the screening programmes was low (about 20%). In the Czech Republic, 97 % of GPs participated in the programme, but only 20% of them have been able to screen at least 50 percent of the target population. The eligibility for screening declines with increasing age, co-morbidity and recently performed colonoscopy. In the age group of 50 to 75, approximately 15 % of patients are non-eligible for screening. Finally, the proportion of FOBT positive patients seem higher in established community programmes than the ratio reported from trials. CRC screening is experiencing a rapid expansion and effective programmes are now available. GPs should play a substantial role in CRC screening either by assessing the risk of their patients, explaining the screening options, or by deciding on the most individually-appropriate strategy within their local health care system. Implications of the population based screening for primary care should be considered and further studied.
Keywords: kolorektální nádory; Europe; okultní krev; Česká republika; Evropa; adherence pacienta; Colorectal Neoplasms; Sigmoidoscopy; Czech Republic; Mass Screening; primární zdravotní péče; sigmoidoskopie; Humans; Occult Blood; Guideline Adherence; Practice Patterns, Physicians'; Patient Compliance; dodržování směrnic; plošný screening; Primary Health Care; lékařská praxe - způsoby provádění; lidé